Current surgical treatment policy in invasive bronchopulmonary aspergillosis - M. D. Ter-Ovanesov; O. D. Zakharov; B. Ye. Polotsky; M. A. Volkova; I. Ye. Tyurin (Онкогематология)
Invasive aspergillosis is one of the most life-threatening complications of treatment of oncohematological diseases. In the literature there is no consensus of treatment options and indications for surgical treatment. The authors have observed 2 cases of invasive aspergillosis in patients with acute myeloid leukemia. Both patients needed pneumonectomy but the first of them received only conservative therapy because of bad general condition and died of pulmonary hemorrhage. In the second case primary lobectomy and postoperative reatment with caspofungin led to recovery and permitted to continue chemotherapy. Now this patient is in complete remission of acute myeloid leukemia.